Fatal Mesenteric Ischemia Induced by Synthetic Cannabinoids: A Case Report and Literature Review. (18th December 2017) - Hakimian, David; Tomer, Orr; Hiller, Nurith; Heyman, Samuel N.; Israel, Sarah
Abstract : Worldwide use of synthetic cannabinoids (SCs) is rapidly increasing, in part due to the generation of numerous new compounds, sidestepping legal restrictions. Their detection using standard toxicology panels is difficult, due to their vast heterogeneity and lack of structural resemblance to cannabinoids. Sympathetic overactivity and arterial spasm play a role in some of the life-threatening reactions to SCs, such as coronary or cerebral vasoconstriction. Here we report a patient with repeated consumption of SCs that led to mesenteric ischemia and death. A 29-year-old man was frequently evaluated in the Emergency Medicine Department for recurrent transient crampy abdominal pain, associated with the use of the SCs colloquially known as "Mr. Nice Guy." He was finally hospitalized with a protracted attack, associated with diarrhea and leukocytosis. Initial evaluation including computed tomography was unremarkable. Diarrhea and leukocytosis gradually resolved, but bouts of hypertension and abdominal pain occurred in association with repeated consumption of the SCs. On the fifth hospital day, the patient developed abrupt abdominal pain, associated with profound shock and signs of peritoneal irritation and succumbed within an hour. Postmortem CT scan was consistent with intestinal perforation most probably due to a nonobstructive mesenteric infarction. There was no evidence of a single vessel infarction.